A Study of (R,S)-Bimodules Homomorphisms (Jurnal Matematika, Statistika dan Komputasi, 2026)
This paper discusses the generalization of the fundamental theorems of -module homomorphisms to the structure of -bimodules, where  and  are rings with identity. The study begins with a review of the definitions, properties, and types of -bimodule homomorphisms. Subsequently, three fundamental theorems of -module homomorphisms are generalized to the -bimodule setting. The results show that the fundamental structures and relationships in module theory can be naturally extended to bimodules by considering the actions of two rings that are compatible with the bimodule operations. This generalization provides a broader framework for studying algebraic structures involving two interacting ring actions.This paper discusses the generalization of the fundamental theorems of -module homomorphisms to the structure of -bimodules, where  and  are rings with identity. The study begins with a review of the definitions, properties, and types of -bimodule homomorphisms. Subsequently, three fundamental theorems of -module homomorphisms are generalized to the -bimodule setting. The results show that the fundamental structures and relationships in module theory can be naturally extended to bimodules by considering the actions of two rings that are compatible with the bimodule operations. This generalization provides a broader framework for studying algebraic structures involving two interacting ring actions.
Keywords: homomorphism; isomorphism; epimorphism; bimodules